2014
DOI: 10.1021/am5021233
|View full text |Cite
|
Sign up to set email alerts
|

Do Transition Metal Carbonates Have Greater Lithium Storage Capability Than Oxides? A Case Study of Monodisperse CoCO3 and CoO Microspindles

Abstract: As substitutions for transition metal oxides (MOs), transition metal carbonates (MCO3) have been attracting more and more attention because of their lithium storage ability in recent years. Is MCO3 better than MOs for lithium storage? To answer this question, monodisperse CoCO3 and CoO microspindles with comparable structures were synthesized and investigated as a case study. Excluding its structural effect, we found CoCO3 still exhibited reversible capacities and rate capabilities much higher than those of Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 55 publications
2
66
0
Order By: Relevance
“…It has been proved that the practical capacities of some MCO 3 products are as high as or even higher than the corresponding transition metal oxides (MO) [7,9,10,18,20]. For example, the 10th reversible capacity of microspindle-like CoCO 3 could reach 1065 mAh g À1 , higher than that of microspindle-shaped CoO (~720 mAh g À1 ) operated at a same rate of 50 mA g À1 [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proved that the practical capacities of some MCO 3 products are as high as or even higher than the corresponding transition metal oxides (MO) [7,9,10,18,20]. For example, the 10th reversible capacity of microspindle-like CoCO 3 could reach 1065 mAh g À1 , higher than that of microspindle-shaped CoO (~720 mAh g À1 ) operated at a same rate of 50 mA g À1 [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that the practical capacities of some MCO 3 products are as high as or even higher than the corresponding transition metal oxides (MO) [7,9,10,18,20]. For example, the 10th reversible capacity of microspindle-like CoCO 3 could reach 1065 mAh g À1 , higher than that of microspindle-shaped CoO (~720 mAh g À1 ) operated at a same rate of 50 mA g À1 [18]. More interestingly, most of the reported capacities of MCO 3 are higher than the calculated theoretical capacity (~450 mAh g À1 ) according to the traditional conversion reaction mechanism ðMCO 3 þ 2Li4Li 2 CO 3 þ MÞ, which indicates there must be novel mechanisms for lithium storage in MCO 3 [7e10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhou et al proposed that newly-generated Fe 0 nanoparticles could work as electrochemical catalysts for the reversible conversion of some SEI components, especially Li 2 CO 3 [40]. Furthermore, it was found that the reversible transformation depended on the types of metal catalysts present [16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Although transition-metal oxalates show high operating potentials like transition-metal oxides as anode materials, leading to the voltage and energy density of full cells to decrease (when combined with cathodes such as LiCoO 2 ), they possess attractive features to make up for this shortcoming. Recent works have shown that they often have even greater lithium storage capabilities than those of oxides [19][20][21]. Among oxalates, anhydrous CoC 2 O 4 has been considered one of the most important new electrode materials because it can deliver reversible capacities of up to three times higher than graphite.…”
Section: Introductionmentioning
confidence: 99%
“…The most common solution is preparing the composites consisting of transition metal carbonates and conductive carbon (such as amorphous carbon [17], graphene [14,18], carbon nanotubes [19,20]) to improve conductivity of electrodes. As a typical metal carbonate, CoCO 3 also presents good promise as anode material of LIBs owing to high specific capacity of 1000 mAh g À1 which is higher than its theoretical value (466 mAh g À1 ) [21]. Similar to most transition metal carbonate, CoCO 3 also presents poor electronic conductivity and suffers from severe volume variation and particle aggregation with cycling, thus leading to rapid disintegration of the electrode and capacity fading.…”
Section: Introductionmentioning
confidence: 99%